Aberrant expression of MRAS and HEG1 as the biomarkers for osimertinib resistance in LUAD - Mingxin Liu; Bo Tang; Run Xiang; Peihong Hu; Chuan Xu; Lanlin Hu; Qiang Li (Discover Oncology)
Abstract Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) are the most applied targeted therapy for EGFR-mutant lung adenocarcinoma (LUAD). The third-generation EGFR-TKI, osimertinib, is widely used throughout lung cancer treatment, with single or combination modes. One of the main barriers in osimertinib treatment is the acquired resistance and mechanisms are not fully understood. Gene expression other than genetic mutations might predict drug response and mediate resistance occurrence. We analyzed six datasets of osimertinib-resistant LUAD cells from the Gene Expression Omnibus (GEO) database and identified two hub genes, named MRAS and HEG1. We found that the expression mode of MRAS/HEG1 in LUAD was osimertinib-dependent and contributed to drug resistance. We also explored potential mechanisms of hub genes related osimertinib resistance and emphasized the M2 infiltration involved. Moreover, potential therapeutic agents conquering MRAS/HEG1-related resistance were also identified. In conclusion, MRAS and HEG1 might be responsible for osimertinib resistance and could be promising prognostic biomarkers for osimertinib response in LUAD, which might provide insights into therapeutic strategies.